HIGH-FREQUENCY RESPONSE OF COMPLEX INITIAL PERMEABILITY OF Cr SUBSTITUTED Co0.5Cu0.5Fe2-xCrxO4 - Khan, M H R; Hossain, A K M Akther (Bangladesh Journal of Physics, 2025)
The Lattice parameter, density, initial permeability, saturation magnetization, and Néel temperature of the Cr substituted various Co0.5Cu0.5Fe2-xCrxO4 have been invented. It also explores how the sintering temperature affects these samples' density, porosity, grain size, and initial permeability. As the Cr content increases, the lattice parameter, density, and saturation magnetization decrease. The variation of lattice parameters, density, and maximum magnetic saturation level can be explained in the light of ionic size, atomic mass, and magnetic moment of Cr ion, respectively. However, grain size, complex initial permeability, and coercivity rise until x=0.2 and fall as the Cr concentration increases. Grain size, initial permeability, and coercivity correlated to each other. The textured structure of this ferrite was found at 1373K, confirmed by XRD and microstructural analysis. Bangladesh Journal of Physics, Vol. 29, Issue 1, pp. 25 – 38, June 2022